Odpowiedzi

2010-04-07T13:57:00+02:00
A+b+c=27
c=a+b+9
b= (a+c)/2 +3
a=27-b-c

c=27-b-c+b+9
c+c=27+9
2c=36/2
c=16

b=(27-b-b+c)/2 +3
b=(27-b)/2 +3
b-3=(27-b)/2
2(b-3)=27-b
2b-6=27-b
3b=27+6
3b=33/3
b= 11

a=27-b-c
a=27-11-16
a=0
3 1 3
2010-04-07T14:02:48+02:00
A +b +c = 27 --> a = 27 - b - c
c = [a+b]/2 + 3 , mnożę obie strony równości przez 2
b = [a+c]/2 - 3 , mnożę obie strony równości przez 2
------------------------------------------------------------------
a = 27 - b - c
2c = a+b +6
2b = a+c -6
-------------------------
2c = (27-b-c) +b +6
2b =(27 -b -c) +c - 6
--------------------------
2c = 33 - c --> 3c = 33
c = 11
2b = 21 - b ---> 3b = 21
b = 7
a = 27 - b -c = 27 - 7 - 11 = 9

Odp. a = 9, b = 7 , c = 11
5 5 5